An Evaluation on Implemention of STBM Program Pillar 1 to Decrease of Diarrhea at ODF Village (Reinforcing Factors on Precede – Proceed) in Bondowoso District - Titit Pramiasih; Sri Hernawati; Isa Ma'rufi (Health Notions, 2019)
Diarrhea is still a health problem which is found in almost the whole world, especially in developing countries including to Indonesia. National Strategy Policies of STBM refers to a strategy of acceleration which aims to pursue targets of SDGs. STBM is an integrated action to decrease number of diarrhea incident and to improve hygiene and optimal quality of society life. This research aims to evaluate implementation of program STBM Pillar 1 by identifying factors that are able to influence to behavior of free defecation in ODF Village, Bondowoso District. This study uses a quantitative approach. This type of research is observational analytic using cross-sectional design, to identify the factors that influence the behavior of free defecation which is the cause of the high incidence of diarrhea in ODF villages. The study population was all diarrhea sufferers in the ODF village in Bondowoso district, with a population size of 3293 people. sample size is 350 people selected by cluster random sampling technique. Data was collected through interviews and observations, then analyzed using logistic regression tests. From the research findings, it shows that there were effects of the role of health officers (p-value = 0.006) and village head support (p-value = 0.000) on the behavior of free defecation. Next, the factor of public figure contribution (p-value = 0.304) and religious figure (p-value = 0.268) did not affect to the behavior of free defecation. The researcher recommends that within implementation of STBM program in Bondowoso District must be more focus on the improvement of health officer role and more support from the village head which is completed by clear and appropriate advocacy and regulation. The program of STBM is taken as a program which highlights that society empowerment must keep heading toward STBM principles where the government should completely mobilize existing resources in society, so it will realize independent society to improve their health degree. The village head must also get advocacy in order to be more aware of society health problems. It is hopefully able to make them realize that their duty is not always due to routine activities such as road construction, paving installment, or other physical activities. Keywords: STBM; behavior; ODF village; diarrhea